2021
DOI: 10.1037/emo0000762
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous vocal expressions from everyday life convey discrete emotions to listeners.

Abstract: Emotional expression is crucial for social interaction. Yet researchers disagree about whether nonverbal expressions truly reflect felt emotions and whether they convey discrete emotions to perceivers in everyday life. In the present study, 384 clips of vocal expression recorded in a field setting were rated by the speakers themselves and by naïve listeners with regard to their emotional contents. Results suggested that most expressions in everyday life are reflective of felt emotions in speakers. Seventy-thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…Vocal cues such as emotional prosody, or “tone of voice”, as well as non-verbal expressions of emotions such as a sigh or laugh, likewise carry significant clues to a speaker’s internal state [ 85 , 86 ]. One study found that participants were able to perceive emotions from audio clips of naturalistic conversations with a high degree of accuracy [ 87 ]. Moreover, the more intensely an emotion was expressed verbally, the higher the accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal cues such as emotional prosody, or “tone of voice”, as well as non-verbal expressions of emotions such as a sigh or laugh, likewise carry significant clues to a speaker’s internal state [ 85 , 86 ]. One study found that participants were able to perceive emotions from audio clips of naturalistic conversations with a high degree of accuracy [ 87 ]. Moreover, the more intensely an emotion was expressed verbally, the higher the accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, different emotions have different prosodic profiles, which listeners can use to determine the speaker's emotional state. Consistent with the latter, Juslin et al [26] showed that participants could recognize and name different emotions with a high degree of accuracy using only audio clips containing natural conversations.…”
Section: Influence Of Facial Masks On Facial Expressions As An Expres...mentioning
confidence: 77%
“…11 Relatively small numbers of acoustic parameters (related to frequency, intensity, spectral balance, and temporal) can predict several emotion categories expressed through speech prosody. 12 Findings related to acoustic parameters are relatively consistent across emotions. Anger, happiness, and fear are described by relatively high mean amplitude, and relatively high pitch, 2−4,13,14 while sadness has been described as having a comparatively low pitch, and low amplitude.…”
Section: Emotions and Emotional Prosodymentioning
confidence: 86%